Total hemoglobin mass, aerobic capacity, and the HBB gene in Polish road cyclists - Malczewska-Lenczowska, J.; Orysiak, J.; Majorczyk, E.; Zdanowicz, R.; Szczepanska, B.; Starczewski, M.; Kaczmarski, J.; Dybek, T.; Pokrywka, A.; Ahmetov, I. I.; Sitkowski, D. (The Journal of Strength and Conditioning Research, 2016)
The relationship between genes, amount of hemoglobin, and physical performance are still not clearly defined. The aim of this study was to examine the association between-551C/T and intron 2, +16 C/G polymorphisms in the beta hemoglobin (HBB) gene and total hemoglobin mass (tHbmass) and aerobic capacity in endurance athletes. Total hemoglobin mass and aerobic capacity indices, i.e.,V[O2max, oxygen uptake at anaerobic threshold (VO2AT), maximal power output (Pmax), and power at anaerobic threshold (PAT) were determined in 89 young road cyclists, female (n = 39) and male (n = 50), who were genotyped for 2 polymorphisms in the HBB gene. The relative values of aerobic capacity indices differed significantly among intron 2, +16 C/G polymorphisms of the HBB gene only in female cyclists; athletes with GG genotype had significantly higher values of VO2max (p = 0.003), VO2AT (p = 0.007), PAT (p = 0.015), and Pmax (p = 0.004) than C carriers. No relationships were found between the C-carrier model (CC + CG vs. GG in the case of intron 2, +16 C/G and CC + CT vs. TT for -551 C/T polymorphisms of the HBB gene) and relative values of tHbmass. Our results demonstrated that the HBB gene could be related to aerobic capacity, but it seems that it does not result from an increase in the amount of hemoglobin in the blood.